Enseñanza-aprendizaje con simulador dental en prácticas de técnicas anestésicas del maxilar inferior. Carrera de Odontología. UNL. Periodo abril-septiembre 2023 - Chuncho Villavicencio, Sandra Janeth (2024)
In the field of dentistry, clinical simulation is recognized as an innovative and essential tool for professional education. It provides a practical and experimental foundation that allows students to experience a more realistic and immersive learning environment. The objective of this research project is to assess the importance of employing a dental simulator in the instruction of mandibular anesthesia techniques within the Dentistry program at UNL. Specifically targeting students in the 5th and 6th cycles of the program, the study covers the period from April to September 2023. A quantitative approach is used to develop a framework for evaluating the effectiveness of the dental simulator. Information is gathered through preand post-experimental surveys, which are administered in two phases. In the first phase, a theoretical class on anesthetic techniques is conducted, followed by the pre-experimental survey. The second phase involved practical training using the simulator and included the administration of the post-experimental survey. Throughout both phases, the study group received thorough guidance in both theoretical and practical components. The findings indicate that during the pre-experimental stage, students lacked the necessary knowledge to perform the practice effectively. In contrast, the post-experimental stage showed a marked improvement. This improvement is evidenced by a higher rate of correct responses and favorable evaluations from both students and instructors. As a result, there was a significant increase in the understanding, skill and ability to perform the anesthetic techniques. In summary, the research emphasizes the significant value of using a simulator for students and instructors in the Dentistry program. This approach is vital for success in the clinical component, as it facilitates the acquisition of skills and competencies by integrating practical and theoretical knowledge. Consequently, it offers a more realistic learning experience